Diversified syntheses of multifunctionalized thiazole derivatives via regioselective and programmed C–H activation1. Issue 22 (18th March 2015) - Liu, Xiang-Wei; Shi, Jiang-Ling; Wei, Jiang-Bo; Yang, Chao; Yan, Jia-Xuan; Peng, Kun; Dai, Le; Li, Chen-Guang; Wang, Bi-Qin; Shi, Zhang-Jie
<x xml:space="preserve">Abstract</x> The direct construction of 5-alkenylated thiazole derivatives from 2-/4-substituted thiazole derivatives or challenging thiazole via palladium-catalyzed regioselective 5-alkenylation has been realized.